REVIEWING THE CONCEPT OF JIZYAH: A THEORETICAL APPROACH TO HISTORY - Mohammad Ghozali; Wahyu Nugroho (Univeristas Islam Bandung, 2021)
In the treasures of Islamic civilization, Muslims recognize many State income instruments, one of which is jizyah, which is a contribution that must be paid by unbelievers who settled in the Islamic State to obtain protection and guarantee that they will live there. With the continued development of science and culture, some scholars state that jizyah is only imposed on the book's people, and jizyah is a form of oppression for non-Muslims, even though this is not true. So, this research seeks to present historical facts taken from history books and research that discuss jizyah. This type of research is a literature review using descriptive qualitative methods. As for the results of the study, that the initial stipulation of jizyah was at the time of the Prophet precisely after the Tabuk war event in 9 H. Then the jizyah continued during the time of Khulafa Rasyidin and continued to grow, especially during the Caliph Umar regarding the provisions of jizyah applicable from those previously imposed on group representation to each capable non-Muslim people. Then, jizyah's wisdom and purpose are contained in Al-Quran Surah At-Taubah verse 29, that with the existence of jizyah, the non-Muslims are given life protection in an Islamic state. With jizyah, non-Muslims get security, comfort, convenience in dealing with Muslims, welfare, and security guarantees for their property.